2020
DOI: 10.1039/d0tc00429d
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid organic–inorganic silsesquioxane and cobalt(ii) tetrasulphophthalocyanine material as an efficient electrochemical sensor for the simultaneous determination of the anti-hypertensive nifedipine and its metabolite

Abstract: A novel electrochemical sensor was applied to determination of anti-hypertensive nifedipine through reduction in the presence of its main metabolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…These data suggest that the molecular mechanism involved in the biological activity produced by the diazocine derivative could be in a different manner compared to those drugs. Analyzing these data and other studies which indicate that some diazocine derivatives can exert changes in the cardiovascular system and blood pressure through calcium channel activation (9,10); for this reason, in this study the biological activity exerted by diazocine in the absence or presence of nifedipine (type-L calcium channel inhibitor) [28,29] on left ventricular pressure was evaluated using an isolated rat heart model. The results showed that diazocine derivative exerts changes on left ventricular pressure and this phenomenon was not inhibited by nifedipine; these data suggest that diazocine does not exert its effect on left ventricular pressure through activation of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the molecular mechanism involved in the biological activity produced by the diazocine derivative could be in a different manner compared to those drugs. Analyzing these data and other studies which indicate that some diazocine derivatives can exert changes in the cardiovascular system and blood pressure through calcium channel activation (9,10); for this reason, in this study the biological activity exerted by diazocine in the absence or presence of nifedipine (type-L calcium channel inhibitor) [28,29] on left ventricular pressure was evaluated using an isolated rat heart model. The results showed that diazocine derivative exerts changes on left ventricular pressure and this phenomenon was not inhibited by nifedipine; these data suggest that diazocine does not exert its effect on left ventricular pressure through activation of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…[ 121 ] Some biosensors based on hybrid materials playedan important role in drug analysis, such as analysis of drug composition and detection of corresponding metabolites. [ 122,123 ] In addition to monitoring biomolecules, biosensors can also measure the electrical charge or bioelectrical signals of organs through noninvasive skin ways. Biosensor based on field‐effect transistor (FET) structures has become one of the most attractive biological electronic devices because of the least energy consumption and the fastest testing time.…”
Section: Application Of Flexible Sensors Based On Hybrid Materialsmentioning
confidence: 99%
“…[22][23][24] Additionally, the presence of the nitrophenyl group in nifedipine, as an electroactive group, led to the development of analytical methods and the identification of nifedipine by electrochemical methods. [25][26][27] Modification of the electrode surface is a useful way for highly enhancing the electrochemical signal due to increasing surface area and also electron transfer rate. [28][29][30] Moreover, by modifying the surface of different electrodes, parameters like selectivity and sensitivity of the target species can be improved.…”
Section: Introductionmentioning
confidence: 99%